Goodwill impairment: an examination of chief executive officer tenure in Malaysia - Al-Hiyari, Ahmad; Abdul Latif, Rohaida; Amran, Noor Afza (American Scientific Publishers, 2016)
Accounting for purchased goodwill has changed from amortisation to impairment approach.The standard setters argue that the impairment-only approach will better reflect the underlying economic attributes of goodwill.However, due to the great subjectivity involved in fair values estimate, the impairment approach is susceptible to manipulation. We examine the influence of chief executive officer (CEO) tenure on the amount of goodwill impairment for a sample of 727 companies listed on Bursa Malaysia from years 2011 to 2012. Our empirical results are contradictory to previous research findings that CEOs with shorter tenure are insignificantly associated with magnitude of goodwill impairment. Further analysis reveals that new CEOs are associated with a greater magnitude of impairments only when earnings are positive.The result is consistent with the premise of new CEOs involving in income smoothing, where the incentives to expense goodwill is greatest for profitable firms.